Multi-Agent Framework in Visual Sensor Networks. (5th November 2006) - Patricio Patricio, M. A. M. A.; Carbó Carbó, J. J.; Pérez Pérez, O. O.; García García, J. J.; Molina Molina, J. M. J. M.
Abstract : The recent interest in the surveillance of public, military, and commercial scenarios is increasing the need to develop and deploy intelligent and/or automated distributed visual surveillance systems. Many applications based on distributed resources use the so-called software agent technology. In this paper, a multi-agent framework is applied to coordinate videocamera-based surveillance. The ability to coordinate agents improves the global image and task distribution efficiency. In our proposal, a software agent is embedded in each camera and controls the capture parameters. Then coordination is based on the exchange of high-level messages among agents. Agents use an internal symbolic model to interpret the current situation from the messages from all other agents to improve global coordination.